Two module electromagnetic launcher with pneumatic assist. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski; Krzysztof Zawirski, Andrzej; Kluszczynski, K.; Domin, Jarosław
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a new concept of a multi-module electromagnetic launcher with pneumatic assist. The authors focus on the problem of modelling a two-module electromagnetic launcher consisting of a coil-gun (module C) and a rail-gun (module R), as well as on the key problem of determining their position-dependent parameters, i.e. the resistances and inductances of discharging electrical circuits connected with the both modules. Special attention is paid to the possibility of influencing the missile's flight via basic controller variation of the initial voltage values across the terminals of the capacitor batteries supplying current to both modules C and R. Design/methodology/approach – Analysis of the electromagnetic launcher has been based on the circuit-field approach. Differential equations describing movement of the missile have been drawn from circuit theory. The Finite Element Method and the Comsol Multiphysic program were used to determine position-dependent parameters in module C. It is worth emphasising that the effect of saturation (resulting from B-H curve for ferromagnetic part of the considered magnetic circuit) was taken into account. The influence of the initial missile speed adjusted in a pneumatic assist unit on the missile's velocity was also considered and illustrated by appropriate simulations (the Matlab program). Findings – In analysing the flight of a missile along coil-gun and rail-gun modules, it is necessary to distinguish between three specific stages of the moveable element: the "fall in" stage, the "drive through" stage and the "fall out" stage. One of the most important findings is that during modelling, it is necessary to take into account of all the three above-mentioned stages of missile movement and, in particular, the "fall in" stage. It was shown both by computer simulations and laboratory investigations that this stage plays an important role in determining the time curves of decaying currents in discharging electrical circuits of both module C and module R. Research limitations/implications – The main difficulties are related to determining the influence of air drag force upon missile movement (especially in module C), as well as identifying an accurate value for contact resistances and friction force between the rails and the missile in module R. Practical implications – Hybrid construction employing propelling units of different characters should be treated as a promising and challenging trend in developing launcher structure. One of the most significant advantages of such a solution is the possibility of influencing missile velocity during its flight. Social implications – Since the first device was successfully completed in 1920 the continuous rise in the interest on electromagnetic launchers has been observed. As far as their social and technical impact is concerned, one of the most promising fields of interest seem to be launchers of satellites, high-pressure compressors, simulators modelling collisions between meteoroids and the surface of the earth and electromagnetic guns on board war ships. Originality/value – The novel concept in developing the construction of launchers presented in this paper has been to integrate propelling modules of different characteristics and to create a new multi-module constructional-compact whole. The designed and constructed prototype consists of three modules: a pneumatic drive unit and two electromagnetic drive units that have different principles of operation. The original methodology leading to the creation of its effective mathematical model (focusing on determination of position-depended parameters) was presented and verified in an experimental way.